2020
DOI: 10.3389/fpubh.2019.00396
|View full text |Cite
|
Sign up to set email alerts
|

How Much Education Is Needed to Delay Women's Age at Marriage and First Pregnancy?

Abstract: Background It is common for older people to become grandparents in later life. However, the impacts of grandparenting on their health and well-being remain under-investigated, especially in Chinese society where family is in the core of culture. The current study explored the relationship between grandparenthood and Chinese older people's health and psychological well-being in Hong Kong. Methods Data was collected from a sample of 1,208 Hong Kong Chinese older people aged 55 and above through a telephone surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…Women's education and the timing of their marriage are likely to be closely related (A. A. Marphatia et al, 2020; Raj, McDougal, Silverman, & Rusch, 2014) and this relationship may be bidirectional, although data on the timing of these decisions and events are usually not collected (Sekine & Hodgkin, 2017; Wodon et al, 2017). Moreover, there was no confounding of women's education in the analysis of uneducated women, and the similar magnitude of the effect between the age variables and height of this group and the whole sample suggests the association of education with height is independent.…”
Section: Discussionmentioning
confidence: 99%
“…Women's education and the timing of their marriage are likely to be closely related (A. A. Marphatia et al, 2020; Raj, McDougal, Silverman, & Rusch, 2014) and this relationship may be bidirectional, although data on the timing of these decisions and events are usually not collected (Sekine & Hodgkin, 2017; Wodon et al, 2017). Moreover, there was no confounding of women's education in the analysis of uneducated women, and the similar magnitude of the effect between the age variables and height of this group and the whole sample suggests the association of education with height is independent.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a recent study from Nepal showing that women need to complete grade 9, and ideally grade 11, to substantially increase their odds of marrying after 18 years. 35 Two other studies using DHS data from multiple countries in South Asia found that secondary education but not primary education was strongly protective against marrying early. 17,22 However, our finding that 15-40% (depending on the country) of women who complete 10 or more years of education continue to marry early suggests that actions to address EM must go beyond promoting secondary school completion for girls.…”
Section: Unequal Progress In Eliminating Em and Ecbmentioning
confidence: 98%
“…In Hong Kong, the traditional ideal image of 'two-child family' has been waning (Chen & Yip, 2017). Women's increasing levels of education are associated with delayed marriage and childbirth (Choi, 2018;Marphatia et al, 2020). High costs of child rearing also prevent some young people from having children (Basten & Jiang, 2015;Min & Taylor, 2018).…”
Section: Discussionmentioning
confidence: 99%